Mastering business for strategic communicators : insights and advice from the C-suite of leading brands - Ragas, Matthew W., 1977-; Culp, Ron, 1947- (Emerald Publishing Limited, 2018)
"The most successful communication professionals today are no longer just experts at communication, but are masters of business. To serve as trusted advisors to the C-suite that help align and integrate cross-functional teams and departments across the enterprise behind business goals, communicators need a strong grounding in business acumen. Mastering Business for Strategic Communicators provides readers with expert insights on the various major business functions from the top strategic communication leaders who have been there and done that. This collection of 20 essays from current and former chief communications officers (CCOs) focuses on the business areas that strategic communication helps integrate, connect, and translate across the organization and to external stakeholders: the CEO and the board of directors, marketing, human resources, technology, finance and accounting, legal and regulatory, sales and business operations, research and development, and corporate strategy. From the top senior strategic communication leaders from well-known multinational companies, such as Chevron, GE, GM, McDonald's, Starbucks, Southwest Airlines, Beam Suntory, ConAgra, Cargill, USAA and Walgreens, each contributor writes about his/her experience working with and mastering one of the above areas and also about their professional individual career journey. Each chapter provides readers with a broad view of the collective essential business knowledge needed for strategic communication success, proving essential reading for students of strategic communications, public relations, advertising, marketing, and mass communications, as well as professionals in these fields."--